HA

cho A=\(\frac{3}{x+3}+\frac{1}{x-3}-\frac{18}{9-x^2}\)

a.rút gọn A

b.Tìm x để A=4

H24
25 tháng 5 2017 lúc 13:41

A= \(\frac{3\left(x-3\right)+\left(x+3\right)}{\left(x+3\right)\left(x-3\right)}-\frac{18}{\left(9-x^2\right)}\)

A= \(\frac{3x-9+x+3}{\left(x-3\right)\left(x+3\right)}+\frac{18}{x^2-9}\)

A=\(\frac{3x+x-9+3}{\left(x-3\right)\left(x+3\right)}+\frac{18}{\left(x-3\right)\left(x+3\right)}\)

A=\(\frac{4x+12}{\left(x-3\right)\left(x+3\right)}\)

A=\(\frac{4\left(x+3\right)}{\left(x-3\right)\left(x+3\right)}\)

A=\(\frac{4}{\left(x-3\right)}\)

để A=4

=>   \(\frac{4}{x-3}=4\)

<=>  x-3=1

<=> x=4

Bình luận (0)
CX
25 tháng 5 2017 lúc 13:48

a, Rút gọn : 

\(A=\frac{3}{x+3}+\frac{1}{x-3}-\frac{18}{9-x^2}\)

\(A=\frac{3\left(x-3\right)}{\left(x+3\right)\left(x-3\right)}+\frac{1\left(x+3\right)}{\left(x+3\right)\left(x-3\right)}+\frac{18}{\left(x+3\right)\left(x-3\right)}\)

\(A=\frac{3x-9+x+3+18}{\left(x+3\right)\left(x-3\right)}\)

\(A=\frac{4x+12}{\left(x+3\right)\left(x-3\right)}\)

\(A=\frac{4\left(x+3\right)}{\left(x+3\right)\left(x-3\right)}\)

\(A=\frac{4}{x-3}\)

b, Để A = 4 

\(\Leftrightarrow\frac{4}{x-3}=4\)

\(\Leftrightarrow4\left(x-3\right)=4\)

\(\Leftrightarrow4x-12=4\)

\(\Leftrightarrow4x=16\)

\(\Leftrightarrow x=4\)

Vậy để a = 4 thì x = 4

Bình luận (0)

Các câu hỏi tương tự
TL
Xem chi tiết
TC
Xem chi tiết
H24
Xem chi tiết
HA
Xem chi tiết
H24
Xem chi tiết
LN
Xem chi tiết
PG
Xem chi tiết
LN
Xem chi tiết
AH
Xem chi tiết